A Pan-Cancer Analysis of Cystatin E/M Reveals Its Dual Functional Effects and Positive Regulation of Epithelial Cell in Human Tumors - Xu, Dahua; Ding, Shun; Cao, Meng; Yu, Xiaorong; Wang, Hong; Qiu, Dongqin; Xu, Zhengyang; Bi, Xiaoman; Mu, Zhonglin; Li, Kongning (Frontiers in Genetics, 2021)
Cystatin E/M (CST6), a representative cysteine protease inhibitor, plays both tumor-promoting and tumor-suppressing functions and is pursued as an epigenetically therapeutic target in special cancer types. However, a comprehensive and systematic analysis for CST6 in pan-cancer level is still lacking. In present study, we explored the expression pattern of CST6 in multiple cancer types across ~10,000 samples from TCGA (The Cancer Genome Atlas) and ~8,000 samples from MMDs (Merged Microarray-acquired Datasets). We found that the dynamic expression alteration of CST6 was consistent with dual function in different types of cancer. In addition, we observed the expression of CST6 was globally regulated by the DNA methylation in its promoter region. CST6 expression was positively correlated with the epithelial cell infiltration, involving in epithelial-to-mesenchymal transition (EMT) and proliferation. The relationship between CST6 and tumor microenvironment was also explored. In particular, we found CST6 serves a protective function in the process of melanoma metastasis. Finally, the clinical association analysis further revealed the dual function of CST6 in cancer, and a combination of the epithelial cell infiltration and CST6 expression could predict the prognosis for SKCM patients. In summary, this first CST6 pan-cancer study improves the understanding of the dual functional effects on CST6 in different types of human cancer.